Simultaneous Molecular and Hypoxia Imaging of Brain Tumors In Vivo Using Spectroscopic Photoacoustic Tomography - Li, Meng-Lin; Oh, Jung-Taek; Xie, Xueyi; Ku, Geng; Wang, Wei; Li, Chun; Lungu, Gina; Stoica, George; Wang, Lihong V. (Proceedings of the IEEE, 2008)
Noninvasive molecular and functional imaging in vivo is promising for detecting and monitoring various physiological conditions in animals and ultimately humans. To this end, we present a novel noninvasive technology, spectroscopic photoacoustic tomography (SPAT), which offers both strong optical absorption contrast and high ultrasonic spatial resolution. Optical contrast allows spectroscopic separation of signal contributions from multiple optical absorbers (e.g., oxyhemoglobin, deoxyhemoglobin, and a molecular contrast agent), thus enabling simultaneous molecular and functional imaging. SPAT successfully imaged with high resolution the distribution of a molecular contrast agent targeting integrin overexpressed in human U87 glioblastomas in nude mouse brains. Simultaneously, SPAT also imaged the hemoglobin oxygen saturation and the total hemoglobin concentration of the vasculature, which revealed hypoxia in tumor neovasculature. Therefore, SPAT can potentially lead to better understanding of the interrelationships between hemodynamics and specific biomarkers associated with tumor progression.